2009
DOI: 10.1158/1055-9965.epi-08-0614
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length, Current Perceived Stress, and Urinary Stress Hormones in Women

Abstract: Telomeres are repetitive DNA sequences that cap and protect the ends of chromosomes; critically short telomeres may lead to cellular senescence or carcinogenic transformation. Previous findings suggest a link between psychosocial stress, shorter telomeres, and chronic disease risk. This cross-sectional study examined relative telomere length in relation to perceived stress and urinary stress hormones in a sample of participants (n = 647) in the National Institute of Environmental Health Sciences Sister Study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
131
4
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 39 publications
7
131
4
2
Order By: Relevance
“…The numbers of men and women in the short TL/high TA groups were similar, but there was no indication of comparable trends in physiological responses (Tables S1 and S2). Studies relating shorter telomeres to life stress have involved both men and women (10,11,14,18,20). Previous research relating telomeres to acute physiological stress responses have been carried out with female but not male samples (15,21,24), although associations between health risk and the combination of shorter telomeres and raised TA have been reported in both men and women (16,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The numbers of men and women in the short TL/high TA groups were similar, but there was no indication of comparable trends in physiological responses (Tables S1 and S2). Studies relating shorter telomeres to life stress have involved both men and women (10,11,14,18,20). Previous research relating telomeres to acute physiological stress responses have been carried out with female but not male samples (15,21,24), although associations between health risk and the combination of shorter telomeres and raised TA have been reported in both men and women (16,25).…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors thought to influence telomere dynamics is psychosocial stress (10,11). Epel et al (12) demonstrated that the severe stress experienced by mothers of chronically ill children was correlated with reduced leukocyte TL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several cross-sectional studies in humans have reported associations between telomere biology and high levels of psychosocial stress exposure (8,17,18) or stress biomarkers (17,19), suggesting that stress-related changes in telomere integrity may be one possible mechanism linking psychosocial stress and agerelated disease (20). Experimentally, high levels of cortisol exposure (a potent stress hormone) have been shown to dampen telomerase activity in leukocytes (21).…”
Section: Developmental Programming | Fetal Originmentioning
confidence: 99%
“…5 The earliest studies demonstrated associations between naturally occurring stressors and telomere biology in noncancer samples, in which stress was associated with shorter TL and lower telomerase activity. 15,16 Although stress plays a role in the etiology and progression of many diseases, [17][18][19] the role of stress in cancer remains suggestive. 20,21 Nonetheless, several biobehavioral pathways between psychosocial stress and mechanisms of cancer development have been indentified.…”
Section: Introductionmentioning
confidence: 99%